The Australian Child & Adolescent Trauma, Loss & Grief - Merritt, S (My University, 2010)
The Australian Child & Adolescent Trauma, Loss & Grief Network (ACATLGN) aims to promote understanding of child and adolescent trauma, loss and grief. It is supported by Australian Government funding under the COAG New Early Intervention Services for Parents, Children and Young People Measure, and is a national network based from the Australian National University. A key component of the network is the Aboriginal and Torres Strait Islander Hub, a web-based resource providing specific resources to address Aboriginal and Torres Strait Islander trauma, loss and grief.
Family Relationships Quarterly Clearinghouse
Keywords: Disadvantage, adversity and resilience; Dsiadvantage, adversity and resilience; Adversity and resilience